Reappraisal of a 2-Cm Cut-off Size for the Management of Cystic Pancreatic Neuroendocrine Neoplasms: A Multicenter International Study. Issue 5 (24th May 2021) - Maggino, Laura; Schmidt, Andrea; Käding, André; Westermark, Sofia; Ceppa, Eugene P.; Falconi, Massimo; Javed, Ammar A.; Landoni, Luca; Pergolini, Ilaria; Perinel, Julie; Vollmer, Charles M.; Sund, Malin; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: The aim of this study was to characterize an international cohort of resected cystic pancreatic neuroendocrine neoplasms (cPanNENs) and identify preoperative predictors of aggressive behavior. Background: The characteristics of cPanNENs are unknown and their clinical management remains unclear. An observational strategy for asymptomatic cPanNENs ≤2 cm has been proposed by recent guidelines, but evidence is scarce and limited to single-institutional series. Methods: Resected cPanNENs (1995–2017) from 16 institutions worldwide were included. Solid lesions (>50% solid component), functional tumors, and MEN-1 patients were excluded. Aggressiveness was defined as lymph node (LN) involvement, G3 grading, distant metastases, and/or recurrence. Results: Overall, 263 resected cPanNENs were included, among which 177 (63.5%) were >2 cm preoperatively. A preoperative diagnosis of cPanNEN was established in 162 cases (61.6%) and was more frequent when patients underwent endoscopic ultrasound [EUS, odds ratio (OR) 2.69, 95% confidence interval (CI) 1.52–4.77] and somatostatin-receptor imaging (OR 3.681, 95% CI 1.809–7.490), and for those managed in specialized institutions (OR 3.12, 95% CI 1.57–6.21). Forty-one cPanNENs (15.6%) were considered aggressive. In the whole cohort, LN involvement on imaging, age >65 years, preoperative size >2 cm, and pancreatic duct dilation were independently associated with aggressive behavior. In asymptomatic patients, older age and a preoperative size >2 cm remained independently associated with aggressiveness. Only 1 of 61 asymptomatic cPanNENs ≤2 cm displayed an aggressive behavior. Conclusions: The diagnostic accuracy of cPanNENs is increased by the use of EUS and somatostatin-receptor imaging and is higher in specialized institutions. Preoperative size >2 cm is independently associated with aggressive behavior. Consequently, a watch-and-wait policy for sporadic asymptomatic cPanNENs ≤2 cm seems justified and safe for most patients.